WQ-3810, a fluoroquinolone with difluoropyridine derivative as the R1 group exerts high potency against quinolone-resistant Campylobacter jejuni - Kentaro Koide; Hyun Kim; Matthew V. X. Whelan; Lawrence P. Belotindos; Wimonrat Tanomsridachchai; Ruchirada Changkwanyeun; Masaru Usui; Tadhg Ó Cróinín; Jeewan Thapa; Chie Nakajima; Yasuhiko Suzuki (Microbiology Spectrum, 2024)
ABSTRACT Quinolone-resistant Campylobacter jejuni have been increasing worldwide. Quinolones exert their antibacterial activity by inhibiting DNA gyrase, but most of the isolates acquire quinolone resistance via an amino acid substitution in the A subunit of DNA gyrase. WQ-3810 is a quinolone antibiotic that has been reported to have high potency even to DNA gyrase with amino acid substitutions in several bacterial species; however, there was no information on C. jejuni. Hence, this study aimed to evaluate the activity of WQ-3810 to inhibit wild-type/mutant DNA gyrases of C. jejuni and the bacterial growth for accessing the potency for the treatment of quinolone-resistant C. jejuni infection. The inhibitory activity of WQ-3810 was assessed and compared with ciprofloxacin and nalidixic acid by calculating the half maximal inhibitory concentration (IC50) against wild-type/mutant DNA gyrases. Next, the minimum inhibitory concentration (MIC) of WQ-3810 and five other quinolones was determined for C. jejuni including quinolone-resistant strains with amino acid substitutions in GyrA. Furthermore, the interaction between WQ-3810 and wild-type/mutant DNA gyrase was speculated using docking simulations. The IC50 of WQ-3810 against wild-type DNA gyrase was 1.03 µg/mL and not different from that of ciprofloxacin. However, those of WQ-3810 against mutant DNA gyrases were much lower than ciprofloxacin. The MICs of WQ-3810 ranged <0.016–0.031 µg/mL and were the lowest against both quinolone-susceptible and quinolone-resistant strains among the examined quinolones. The results obtained by the docking simulation agreed well with this observation. WQ-3810 seems to be a promising antimicrobial agent for the infections caused by quinolone-resistant C. jejuni.IMPORTANCEWQ-3810, a relatively new quinolone antibiotic, demonstrates exceptional antibacterial properties against certain pathogens in previous studies. However, its efficacy against quinolone-resistant Campylobacter jejuni was not previously reported. The prevalence of quinolone-resistant C. jejuni as a cause of foodborne illnesses is increasing, prompting this investigation into the effectiveness of WQ-3810 as a countermeasure. This study revealed high inhibitory activity of WQ-3810 against both wild-type and mutant DNA gyrases of C. jejuni. WQ-3810 was equally efficacious as ciprofloxacin against wild-type DNA gyrases but showed superior effectiveness against mutant DNA gyrases. WQ-3810 also demonstrated the lowest minimum inhibitory concentrations, highlighting its enhanced potency against both susceptible and resistant strains of C. jejuni. This observation was well supported by the results of the in silico analysis. Consequently, WQ-3810 exhibits a higher level of bactericidal activity compared to existing quinolones in combating both susceptible and resistant C. jejuni isolates.